Training and Mentoring Youth in Flavored Banana Chip Production as a Rural Enterprise in Lang-Lang Village - Ayu Rannisa Putri; Evania Suryaningsih; Umi Masruro; Muhammad Syauqillah (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2024)
This training and mentoring program aims to strengthen the entrepreneurial capacity of youth in Lang-Lang Village, Singosari District, Malang Regency, through the production of flavored banana chips. Utilizing the Asset-Based Community Development (ABCD) approach, the program identifies and leverages local assets particularly banana cultivation to develop value-added products. Participants received practical training in banana processing, flavor development, modern packaging techniques, and digital marketing. As a result, the youth improved their technical skills and successfully produced high-quality banana chips with innovative flavors such as chocolate and tiramisu. They also expanded market reach through platforms like Instagram and Shopee. The initiative not only enhances individual entrepreneurial competencies but also contributes to local economic development. This program exemplifies a sustainable and replicable model for community-based economic empowerment by promoting youth engagement, local resource utilization, and digital literacy in rural enterprise development.